2020
DOI: 10.3233/efi-190349
|View full text |Cite
|
Sign up to set email alerts
|

Provision of academic data for research: A step for academic success

Abstract: One of the most widely researched issue on higher education relates to exposed paths that lead to academic success. Nowadays information systems represent an essential part of the education sector in many universities. In particular, the increasing of the number of students in higher education in Portugal leads to the progressive increase of student's data contained in institutional information systems. This article aims to include the use of student data contained in the Fénix information system of a Portugue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…When they complete the first phase, they do not have to make assessments in the second phase, usually an exam. As a limitation during the development of this dissertation, it was observed that one of the problems detected when data collection started was the impossibility of knowing whether the grids present in the tool by Miguel et al [19] belonged to one of these phases or the set of both. For this reason, we started from the assumption that all grids were the first phase and it was from this assumption that the averages of each UC were calculated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When they complete the first phase, they do not have to make assessments in the second phase, usually an exam. As a limitation during the development of this dissertation, it was observed that one of the problems detected when data collection started was the impossibility of knowing whether the grids present in the tool by Miguel et al [19] belonged to one of these phases or the set of both. For this reason, we started from the assumption that all grids were the first phase and it was from this assumption that the averages of each UC were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, it was necessary to proceed to the collection, filtering, and processing of the data. The collection of data related to the averages of the courses between the academic years 2013/2014 and 2017/2018 was obtained through the tool developed in the work described by Miguel, Ramos, Martins and Costa [19] that contained the information regarding the averages of each course in the institution where the investigation took place, among other options. Fig.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation